Defect chemistry and high-temperature thermodynamics of PrBaCo2O6-δ. (October 2021) - Sednev-Lugovets, Anton L.; Sereda, Vladimir V.; Malyshkin, Dmitry A.; Tsvetkov, Dmitry S.; Ivanov, Ivan L.; Zuev, Andrey Yu.; Maignan, Antoine
Highlights: The model function log( p O2 ) = f (δ, T ) can be extrapolated to lower temperatures. The value of Δ h - O was determined by direct oxidation of a sample in the calorimeter. Both calculated and independently determined values of Δ h - O coincide with each other. Oxygen exchange impact on drop calorimetry measurements was assessed. The values of C p ( T ), Δ 298.15 T H o and Δ 298.15 T S o for PrBaCo2 O5.77 were calculated. Abstract: Using the drop calorimetry and differential scanning calorimetry (DSC), the enthalpy increments of pure PrBaCo2 O6-δ double perovskite in air in the temperature range from 365.3 K to 1272.8 K were obtained. As-measured enthalpy increments corresponded to the constant p O2, but variable oxygen content in PrBaCo2 O6-δ (isodynamical conditions). The defect structure analysis yielded the analytical expressions for the equilibrium oxygen partial pressure, log( p O2 ) = f (δ, T ), and the partial molar enthalpy of oxygen, Δ h ¯ O = f ( T, δ) in PrBaCo2 O6-δ, both functions being valid in relatively wide temperature range. The value of Δ h ¯ O at 1273 K was assessed independently by means of direct oxidation of PrBaCo2 O6-δ in the DSC setup, and was found to agree well with Δ h ¯ O calculated from the defect structure model and p O2 – T – δ diagram. The knowledge of Δ h ¯ O = f ( T, δ) allowed recalculating the enthalpy increments for the sample with constant oxygen content, Δ 298.15 T H ∘ (PrBaCo2 O5.77 ), which were fitted with a modified Einstein function. The smoothed values of Δ 298.15 T H ∘, heat capacity Cp ( T ), and entropy increments Δ 298.15 T S ∘ were evaluated and tabulated for PrBaCo2 O5.77 in the temperature range 350 ≤ T /K ≤ 1300. The results obtained can be used for calculating Δ 298.15 T H ∘, Cp ( T ), and Δ 298.15 T S ∘ for PrBaCo2 O6-δ with an arbitrary constant oxygen content.